The Study of the Best Sustainable Economic Alternative for Public Transport in Tartous - Janoud, Ali (Latakia University Journal -Engineering Sciences Series, 2019)
The level of organization of the internal transport in cities is the basis of integrated traffic regulation that reflects the extent of civilized development it has reached, and the modes of transport to meet the growing need for transport. Basically, Tartous city depends on microbuses as public transport, and it was noticed through questionnaires that microbus passengers suffer from various problems such as un comfort safety, overcrowding, noise and environmental pollution… etc. Bus drivers in their turn suffer from many negative effects such as disorganization of journeys, many stops, the high expense of maintenance compared to the income and many others. That is why it is necessary to find other accessible, easy and reasonable choices. In this research ,three cases combination are highlighted ,taking into consideration the total storage then evaluating these choices by using EXPERT CHOISE program which showed the superiority of public bus in all cases instead of the microbus and the mixed solution ,with a percentage of 0,00 which is less than 1% and also it showed the effective role of using the public bus to microbus in the sustainable development and It is superior to the economic impact when applying engineering economic analysis. يُعدّ تنظيم حركة النقل في المدن أساسا للتنظيم المروري المتكامل الذي يعكس مدى التطور الحضاري الذي وصلت إليه هذه المدن، ولذلك من الأهمية بمكان المعرفة والإحاطة الكاملة بكافة المعايير عند اختيار وسائط النقل العام. تعتمد مدينة طرطوس بشكلٍ أساس على الميكرو باصات كواسطة للنقل الجماعي، وقد تبين من خلال الاستبيانات المُعدّة، أن عدم الراحة والأمان والازدحام والضجّة والتلوث البيئي وغيرها.....، مشاكل عديدة يعاني منها ركاب الميكروباص، وأن عدم الانتظام في الرحلات، وكثرة التوقفات وارتفاع تكلفة الصيانة قياساً بالمردود المالي، وغيرها الكثير، جوانب سلبية يعاني منها سائقو الميكروباص، الأمر الذي يحتم دراسة بدائل أخرى موضوعية وسهلة وممكنة. في هذا البحث تم دراسة ثلاث حالات للدمج تراعي تأمين السعة التخديمية، ومن ثم تقييم هذه البدائل باستخدام برنامج EXPERT CHOISE، ليتبين تقدم حافلة النقل العام في كل الحالات كبديل على الميكروباص والحل المختلط، مع نسبة توافق 0.00 وهي أقل من 1%، كما يبرز الدور الكبير لخيَار استخدام حافلات النقل الداخلي على خَيار الميكروباص، في التنمية المستدامة وبشكل يتفوق فيه على الأثر الاقتصادي عند تطبيق التحليل الاقتصادي الهندسي.